Groundwater Level Control with a Simple Fuzzy Control System - Marzan A. Iskandar; Yanti Susanti; Satyanto K. Saptomo; Budi I Setiawan (Jurnal Keteknikan Pertanian, 1999)
This paper proposes a method for controlling groundwater level in order to maintain a certain desired height by using a simple fuzzy control system. The control signal is determined by evaluating the state of water surface height deviatioh from the desired height on a 4 quadrant phase plane. The control signal is then used to determine the number of drainage or irrigation pumps, which must be operated. Simulation using actual datafrom the jield shows that the proposed method is very effective to maintain the desired height of water surface. This method is very simple, therefore it can be easily implemented using a personal computer or a microcontrol/er, or up-loaded to a P LC (Programmable Logic Controller).